Probe
Patent Information
- Application Number
- JP2022019334
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-26
- Filing Date
- 2022-02-10
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2042-02-10
AI Technical Summary
The diffusion of components in Pd, Cu, and Ag alloy probes into solder during repeated electrical connections leads to tip wear and variations in contact resistance, necessitating frequent cleaning and replacement, which reduces inspection efficiency.
A probe composition comprising 15% to 60% Pd, 3% to 79.9% Cu, and 0.1% to 75% of at least one of Ni and Pt, or a Pd and Cu alloy without Ni and Pt, forms a dense metal compound layer at the interface to suppress component diffusion and wear.
This composition effectively reduces component diffusion into solder, minimizing tip wear and maintaining consistent contact resistance, thereby enhancing probe durability and inspection efficiency.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0004] , , , , , ,
[0006] , , , ,
[0005] , , , , , ,
[0001] The present invention relates to a probe.
Background Art
[0002] To inspect an object to be inspected such as an integrated circuit, the object to be inspected may be electrically connected to an inspection substrate via a probe provided in a socket. The probe may contain an alloy of Pd, Cu, and Ag.
[0003] Patent Document 1 describes an example of an alloy of Pd, Cu, and Ag. The alloy described in Patent Document 1 contains 16% or more and 50% or less of Cu, about 35% to about 59% of Pd, and 4% or more of Ag.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] An alloy of Pd, Cu, and Ag may be used as a material constituting a probe. However, when the tip of a probe containing an alloy of Pd, Cu, and Ag is repeatedly brought into contact with the solder of an object to be inspected for electrical connection, components such as Sn contained in the solder and components contained in the probe tend to diffuse into each other due to factors such as Joule heat. When the components contained in the probe diffuse, the tip of the probe may be worn out. When the tip of the probe is worn out, fluctuations in the contact resistance between the probe and the solder may occur. Therefore, when a probe containing an alloy of Pd, Cu, and Ag is used, the number of times of cleaning or replacement of the tip of the probe becomes relatively large, and the inspection efficiency may decrease.
[0006] One example of the object of the present invention is to suppress the diffusion of components contained in the probe into the solder. Other objects of the present invention will become apparent from the description herein. [Means for solving the problem]
[0007] One aspect of the present invention is, Pd in an amount of 15% to 60% by mass, Cu in an amount of 3% to 79.9% by mass, At least one of Ni and Pt in an amount of 0.1% to 75% by mass, This is a probe that includes [something]. [Effects of the Invention]
[0008] According to the above embodiment of the present invention, the diffusion of components contained in the probe into the solder can be suppressed. [Brief explanation of the drawing]
[0009] [Figure 1] This is a cross-sectional view of the socket according to the embodiment. [Figure 2] This is a cross-sectional view of the socket according to the first modified example. [Figure 3] This is a cross-sectional view of the probe according to a second modified example. [Figure 4] This graph shows the relationship between the mass ratio of Ni contained in the test material and the resistivity of the test material for Examples 2-4, in which the mass ratio of Pd contained in the test material is 45% by mass. [Figure 5] This graph shows the relationship between the mass ratio of Pd contained in the test material and the hardness of the test material for Examples 3, 6, and 10, where the mass ratio of Ni in the test material is 10% by mass, and Examples 7 and 11, where the mass ratio of Ni in the test material is 1% by mass. [Figure 6]This graph shows the relationship between the mass ratio of Ni contained in the test material and the thickness of the diffusion layer between the test material and the solder, for Examples 2-4, where the mass ratio of Pd in the test material is 45% by mass; Examples 5-8, where the mass ratio of Pd in the test material is 35% by mass; and Examples 10-11, where the mass ratio of Pd in the test material is 25% by mass. [Figure 7] This is a magnified view of a portion of the graph shown in Figure 6. [Figure 8] This graph shows the relationship between the mass ratio of Pd contained in the test material and the thickness of the diffusion layer between the test material and the solder, for Examples 3, 6, and 10, and Comparative Example 3, in which the test material does not contain Pt but contains 10 mass% Ni. [Figure 9] This is a triangular graph showing the relationship between the mass ratio of Pd, the mass ratio of Cu, and the mass ratio of at least one of Ni and Pt in the test material. [Figure 10] These are side views of the first test pin, the second test pin, and the third test pin. [Figure 11] This figure shows an SEM image of the tip of the contact area of the first test pin after a continuous energization test. [Figure 12] This figure shows an SEM image of the tip of the contact area of the second test pin after a continuous energization test. [Figure 13] This figure shows an SEM image of the tip of the contact area of the third test pin after a continuous energization test. [Figure 14] This figure shows an SEM image of the tip of the contact area of the fourth test pin after the electrical endurance test. [Figure 15] This figure shows an SEM image of the tip of the contact area of the fifth test pin after the electrical endurance test. [Figure 16] This figure shows an SEM image of the tip of the contact area of the sixth test pin after the electrical endurance test. [Modes for carrying out the invention]
[0010] Embodiments and modified examples of the present invention will be described below with reference to the drawings. In all drawings, similar components are denoted by the same reference numerals, and their descriptions are omitted where appropriate.
[0011] In this specification, ordinal numbers such as "first", "second", "third", etc. are attached simply to distinguish components with the same name, unless otherwise specified, and do not mean specific features of the components (e.g., order or importance).
[0012] FIG. 1 is a cross-sectional view of a socket 10 according to an embodiment.
[0013] In FIG. 1, the arrow indicated by "+Z" indicates the upward direction in the vertical direction, and the arrow indicated by "-Z" indicates the downward direction in the vertical direction. Hereinafter, the direction orthogonal to the vertical direction is referred to as the horizontal direction as necessary.
[0014] The socket 10 includes a probe 100 and an insulating support 200. The probe 100 is provided in a through hole formed in the insulating support 200. The probe 100 has a first plunger 110, a second plunger 120, a tube 130, and a spring 140. In FIG. 1, a state in which an inspection object 20 is being inspected by an inspection substrate 30 is shown using the probe 100. Specifically, in the state shown in FIG. 1, the solder ball 22 of the inspection object 20 and the pad 32 of the inspection substrate 30 are electrically connected via the probe 100.
[0015] The tube 130 extends in the vertical direction. The spring 140 is located inside the tube 130. The probe 100 may not have the tube 130. The spring 140 is wound in a spiral around a virtual axis passing through the center of the tube 130 in the vertical direction.
[0016] The first plunger 110 is located on the upper end side of the spring 140. The first plunger 110 is biased upward by the spring 140, that is, away from the second plunger 120. When the object under inspection 20 is being inspected by the inspection board 30, the first plunger 110 is connected to the object under inspection 20, which is located above the probe 100. In this state, the tip, i.e., the upper end, of the first plunger 110 is in contact with the solder balls 22 of the object under inspection 20. In the example shown in Figure 1, the tip of the first plunger 110 has multiple points that are evenly spaced around a virtual axis that passes vertically through the center of the first plunger 110. The shape of the tip of the first plunger 110 is not limited to the example shown in Figure 1.
[0017] The second plunger 120 is located on the lower end side of the spring 140. The second plunger 120 is biased downward by the spring 140, that is, away from the first plunger 110. When the object to be inspected 20 is being inspected by the inspection substrate 30, the second plunger 120 is connected to the inspection substrate 30, which is located below the probe 100. In this state, the tip, i.e., the lower end, of the second plunger 120 is in contact with the pad 32 of the inspection substrate 30. The tip of the second plunger 120 is hemispherical. The shape of the tip of the second plunger 120 is not limited to the example shown in Figure 1.
[0018] The first plunger 110 contains material (A). Material (A) contains 15% to 60% by mass of Pd, 3% to 79.9% by mass of Cu, and at least one of Ni and Pt in 0.1% to 75% by mass. For example, at least the surface of the first plunger 110 is made of material (A). In this example, for example, the entire first plunger 110 may be formed from material (A). Alternatively, material (A) may cover the surface of the first plunger 110 by a treatment such as plating. When material (A) covers the surface of the first plunger 110, the portion of the first plunger 110 covered by material (A) may be made from a material different from material (A). Also, for example, at least the portion of the first plunger 110 that contacts the solder ball 22 may be made of material (A). In this example, for instance, material (A) may be coated only on the surface of the portion of the first plunger 110 that comes into contact with the solder ball 22, by a treatment such as plating.
[0019] The lower limit of the mass ratio of Pd contained in material (A) is determined, for example, from the viewpoint of the corrosion resistance of material (A). The higher the mass ratio of Pd contained in material (A), the higher the corrosion resistance of material (A) tends to be. From the viewpoint of the corrosion resistance of material (A), the lower limit of the mass ratio of Pd contained in material (A) can be set to the values mentioned above. The lower limit of the mass ratio of Pd contained in material (A) may be, for example, 17% by mass, 20% by mass, 25% by mass, or 30% by mass.
[0020] The upper limit of the mass ratio of Pd contained in material (A) is determined, for example, from the viewpoint of suppressing the diffusion between the components contained in material (A) and the components contained in the solder such as the solder ball 22. If the mass ratio of Pd contained in material (A) is higher than a certain ratio, it may become difficult to sufficiently suppress the diffusion between the components contained in material (A) and the components contained in the solder. From these viewpoints, the upper limit of the mass ratio of Pd contained in material (A) can be set to the values described above. The upper limit of the mass ratio of Pd contained in material (A) may be, for example, 55% by mass, 50% by mass, 48% by mass, or 45% by mass.
[0021] The mass ratio of Pd contained in material (A) can be, for example, 17% by mass or more and 55% by mass or less. Alternatively, the mass ratio of Pd contained in material (A) can be, for example, 20% by mass or more and 50% by mass or less.
[0022] The lower limit of the mass ratio of Cu contained in material (A) is determined, for example, from the viewpoint of the hardness of material (A). In some cases, the hardness of material (A) can be improved by using an alloy of Pd and Cu. On the other hand, if the mass ratio of Cu contained in material (A) is lower than a certain ratio, it may be difficult to ensure sufficient hardness of material (A). From the viewpoint of the hardness of material (A), the lower limit of the mass ratio of Cu contained in material (A) can be set to the values mentioned above. The lower limit of the mass ratio of Cu contained in material (A) may be, for example, 5 mass%, 22 mass%, or 30 mass%.
[0023] The upper limit of the mass ratio of Cu contained in material (A) is determined, for example, from the viewpoint of the corrosion resistance of material (A). If the mass ratio of Cu contained in material (A) is higher than a certain ratio, it may become difficult to ensure sufficient corrosion resistance of material (A). From the viewpoint of the corrosion resistance of material (A), the upper limit of the mass ratio of Cu contained in material (A) can be set to the value described above. The upper limit of the mass ratio of Cu contained in material (A) may be, for example, 74% by mass or 65% by mass.
[0024] The mass ratio of Cu contained in material (A) is preferably, for example, 5% by mass or more and 74% by mass or less.
[0025] The lower limit of the mass ratio of at least one of Ni and Pt contained in material (A) is determined, for example, from the viewpoint of suppressing the diffusion of components contained in material (A) into solder such as solder balls 22. The higher the mass ratio of at least one of Ni and Pt contained in material (A), the more the diffusion of components contained in material (A) into solder tends to be suppressed. From the viewpoint of suppressing the diffusion of components contained in material (A) into solder, the lower limit of the mass ratio of at least one of Ni and Pt contained in material (A) can be set to the values described above. The lower limit of the mass ratio of at least one of Ni and Pt contained in material (A) may be, for example, 0.3 mass%, 0.5 mass%, or 1 mass%. Unless otherwise specified, when material (A) contains both Ni and Pt, the mass ratio of at least one of Ni and Pt contained in material (A) means the sum of the mass ratio of Ni contained in material (A) and the mass ratio of Pt contained in material (A).
[0026] The upper limit of the mass ratio of at least one of Ni and Pt contained in material (A) is determined, for example, from the viewpoint of the resistivity of material (A). The resistivity of material (A) containing Ni tends to increase as the mass ratio of Ni contained in material (A) or the total mass ratio of Ni and Pt increases. In particular, the resistivity of material (A) containing Ni increases when the mass ratio of Ni contained in material (A) or the total mass ratio of Ni and Pt exceeds 75 mass%. From the viewpoint of the resistivity of material (A), the upper limit of the mass ratio of at least one of Ni and Pt contained in material (A) can be the values described above. The upper limit of the mass ratio of at least one of Ni and Pt contained in material (A) may be, for example, 70 mass%, 65 mass%, 30 mass%, or 25 mass%.
[0027] The mass ratio of at least one of Ni and Pt contained in material (A) can be, for example, 0.3% by mass or more and 70% by mass or less. Alternatively, the mass ratio of at least one of Ni and Pt contained in material (A) can be, for example, 0.5% by mass or more and 65% by mass or less.
[0028] In this embodiment, the solder ball 22 is formed from Sn-Bi solder. Sn-Bi solder has relatively low hardness. Therefore, the hardness of material (A) is sufficient to be, for example, around 200 HV. The solder ball 22 may also be formed from a solder other than Sn-Bi solder.
[0029] In this embodiment, compared to cases where the first plunger 110 contains an alloy of Pd, Cu, and Ag without containing either Ni or Pt, or an alloy of Pd and Cu without containing either Ni or Pt, the diffusion of components contained in the first plunger 110 into the solder ball 22 at the interface between the tip of the first plunger 110 and the surface of the solder ball 22 can be suppressed. Furthermore, in this embodiment, compared to cases where the first plunger 110 contains an alloy of Pd, Cu, and Ag without containing either Ni or Pt, or an alloy of Pd and Cu without containing either Ni or Pt, the diffusion of components contained in the first plunger 110 into the solder ball 22 is suppressed, thereby suppressing wear of the tip of the first plunger 110.
[0030] Hereafter, as needed, an alloy consisting of Pd, Cu, and Ag without containing either Ni or Pt will be referred to as a PdCuAg alloy. Similarly, as needed, an alloy consisting of Pd and Cu without containing either Ni or Pt will be referred to as a PdCu alloy. PdCuAg alloys are widely and commonly used as probes for semiconductor testing.
[0031] When material (A) is used, the reason why the diffusion of components contained in material (A) into the solder is suppressed compared to when PdCuAg alloy or PdCu alloy is used is presumed to be as follows: When material (A) and solder come into contact, a dense thin film containing metal compounds such as Sn-Ni or Sn-Pt is formed at the interface between material (A) and solder, due to at least one of the Ni and Pt contained in material (A). When this metal compound is present at the interface between material (A) and solder, the diffusion of components contained in material (A) and solder is suppressed by this metal compound compared to when this metal compound is not present at the interface between material (A) and solder. In contrast, when PdCuAg alloy or PdCu alloy is used, the above metal compound is less likely to form. Therefore, in this embodiment, compared to the case where the first plunger 110 contains a PdCuAg alloy or a PdCu alloy, the diffusion of components contained in the first plunger 110 into the solder ball 22 can be suppressed between the tip of the first plunger 110 and the solder ball 22.
[0032] Figure 2 is a cross-sectional view of the socket 10A according to the first modified example. The socket 10A according to this modified example is the same as the probe 100 according to the embodiment, except for the following points.
[0033] An extension portion 112A is provided at the lower end of the first plunger 110A, extending downward from the first plunger 110A. The first plunger 110A and the extension portion 112A are integrally formed. Therefore, both the first plunger 110A and the extension portion 112A contain material (A). A tip head 114A is provided at the lower end of the extension portion 112A. The tip head 114A may or may not contain material (A).
[0034] A base end portion 122A is provided at the upper end of the second plunger 120A. A hole 124A is formed on the upper surface of the base end portion 122A, opening upwards. A locking portion 126A is provided on a part of the inner wall of the base end portion 122A that defines the hole 124A. The horizontal diameter of the locking portion 126A in the hole 124A is narrower than the horizontal diameter of the portion of the hole 124A located below the locking portion 126A. The tip head 114A is recessed below the locking portion 126A in the hole 124A. The tip head 114A is also vertically movable below the locking portion 126A in the hole 124A. The horizontal diameter of the tip head 114A is larger than the horizontal diameter of the locking portion 126A in the hole 124A. Therefore, the locking portion 126A prevents the tip head 114A from coming out upwards from the hole 124A.
[0035] The probe 100A according to this modified example does not have a tube corresponding to the tube 130 of the probe 100 according to the embodiment. The spring 140A is located between the lower end of the first plunger 110A and the upper end of the base end 122A. The spring 140A is also spirally wound around the extension portion 112A. The first plunger 110A, the extension portion 112A and the tip head 114A are biased upward by the spring 140A. The second plunger 120A and the base end 122A are biased downward by the spring 140A.
[0036] Figure 3 is a cross-sectional view of probe 100B according to a second modified example. Probe 100B according to this modified example is the same as probe 100 according to the embodiment, except for the following points.
[0037] In the example shown in Figure 3, the first plunger 110B and the tube 130B are integrated. Therefore, both the first plunger 110B and the tube 130B contain material (A). The first plunger 110B and the tube 130B are biased upward by the spring 140B, that is, away from the second plunger 120B. The second plunger 120B is biased downward by the spring 140B, that is, away from the first plunger 110B.
[0038] The embodiments and modifications of the present invention have been described above with reference to the drawings, but these are merely examples of the present invention, and various other configurations can also be adopted. [Examples]
[0039] One aspect of the present invention will be described based on examples and comparative examples. The present invention is not limited to the following examples.
[0040] Table 1 shows the composition (unit: mass%) of Pd, Cu, Ni, Pt, Ag, and In contained in each test material of Examples 1-20 and Comparative Examples 1-3. [Table 1]
[0041] The test materials for each of Examples 1-20 and Comparative Examples 1-3 were prepared as follows.
[0042] For Example 1, as shown in Table 1, a compound was obtained by blending 48% by mass of Pd, 22% by mass of Cu, and 30% by mass of Ni. For each of Examples 2-20 and Comparative Examples 1-3, a compound was obtained by blending Pd, Cu, Ni, Pt, Ag, and In to the compositions shown in Table 1 for Examples 2-20 and Comparative Examples 1-3. In Table 1, a value of "0" means that the corresponding metal was not included.
[0043] Next, for each of Examples 1 to 20 and Comparative Examples 1 to 3, the above formulations were melted by arc melting in an argon atmosphere to produce alloy ingots.
[0044] Next, for each of Examples 1 to 20 and Comparative Examples 1 to 3, two types of sheet materials were produced by repeating the rolling and heat treatment of the above alloy ingots: a sheet material with a rolling ratio of 75% and a sheet material with a rolling ratio of 90%. The rolling ratio RR is determined according to the following formula (1), where t1 is the thickness of the alloy ingot before rolling and t2 is the thickness of the alloy ingot after rolling. RR = (t1 - t2) / t1 (1)
[0045] Table 2 shows the measurement results for the resistivity of the test material, the hardness of the test material, and the thickness of the diffusion layer between the test material and the solder, for each of Examples 1 to 20 and Comparative Examples 1 to 3. [Table 2]
[0046] For each of Examples 1-20 and Comparative Examples 1-3, the resistivity of the test material was measured by measuring the electrical resistance R of the test material at room temperature and calculating the resistivity ρ according to the following formula (2). ρ = RS / l (2) However, l is the length of the test material in the direction of current flow, and S is the cross-sectional area of the test material perpendicular to the direction of current flow. For resistivity measurement, a sheet material with a rolling ratio of 90% was used as the test material.
[0047] For each of Examples 1-20 and Comparative Examples 1-3, the hardness of the test material was measured using a micro-Vickers hardness tester by applying a load of 200 gf to the center of the surface of the test material for 10 seconds, viewed from a direction parallel to the thickness direction of the test material. For hardness measurement, a sheet material with a rolling ratio of 75% was used as the test material.
[0048] For each of Examples 1-20 and Comparative Examples 1-3, the thickness of the diffusion layer between the test material and the solder was measured as follows. First, Sn-Bi solder was placed on the test material. Next, with the Sn-Bi solder still on the test material, the test material and Si-Bi solder were heat-treated in an N2 atmosphere at 250°C for 1 hour to melt the solder on the test material. Then, the test material was embedded in resin to expose the cross-section containing both the test material and the solder. Next, an EPMA (Electron Probe Micro Analyzer) was used to perform a line analysis of the interface between the test material and the solder in a direction perpendicular to the surface of the test material on which the solder was placed. The diffusion layer was defined as a layer containing both Sn diffusing from the solder and Pd diffusing from the test piece. The thickness of the diffusion layer was measured from the EPMA measurement results. For measuring the thickness of the diffusion layer, a sheet material with a rolling ratio of 75% was used as the test material.
[0049] As shown in Table 2, in Examples 1-20, the resistivity was in the range of 20 μΩ·cm to 70 μΩ·cm. In contrast, in Comparative Examples 1-3, the resistivity was in the range of 20 μΩ·cm to 40 μΩ·cm. From the comparison between Examples 1-20 and Comparative Examples 1-3, it can be said that the resistivity when the test material contains at least one of Ni and Pt is not significantly higher than the resistivity when the test material is a PdCuAg alloy or a PdCu alloy.
[0050] Figure 4 is a graph showing the relationship between the mass ratio of Ni contained in the test material and the resistivity of the test material for Examples 2 to 4, in which the mass ratio of Pd contained in the test material is 45% by mass.
[0051] In Figure 4, the horizontal axis of the graph shows the mass ratio (unit: mass%) of Ni contained in the test material. The vertical axis of the graph shows the resistivity (unit: μΩ·cm) of the test material.
[0052] The circular plots in Figure 4 represent the plots for Examples 2-4. The solid curves in Figure 4 are curves estimated from the trends of the plots for Examples 2-4.
[0053] As shown in Figure 4, the resistivity of the test material tends to increase as the mass ratio of Ni in the test material increases. From the perspective of keeping the resistivity of the test material below 100 μΩ·cm, it can be said that the mass ratio of Ni in the test material needs to be 35% by mass or less.
[0054] As shown in Table 2, the hardness in Examples 1-20 ranged from 210 HV to 390 HV. In contrast, the hardness in Comparative Examples 1-3 ranged from 270 HV to 350 HV. From a comparison of Examples 1-20 and Comparative Examples 1-3, it can be said that the hardness of the test material containing at least one of Ni and Pt can be made approximately equivalent to the hardness of the test material if it is a PdCuAg alloy or a PdCu alloy.
[0055] Figure 5 is a graph showing the relationship between the mass ratio of Pd contained in the test material and the hardness of the test material for Examples 3, 6, and 10, in which the mass ratio of Ni contained in the test material is 10% by mass, and for Examples 7 and 11, in which the mass ratio of Ni contained in the test material is 1% by mass.
[0056] In Figure 5, the horizontal axis of the graph shows the mass ratio (in mass%) of Pd contained in the test material. The vertical axis of the graph shows the hardness (in HV) of the test material.
[0057] The black circle plots in Figure 5 represent the plots for Examples 3, 6, and 10. The white circle plots in Figure 5 represent the plots for Examples 7 and 11. The straight line labeled "10 mass% Ni" in Figure 5 is a straight line estimated from the trends of the plots for Examples 3, 6, and 10. The straight line labeled "1 mass% Ni" in Figure 5 is a straight line estimated from the trends of the plots for Examples 7 and 11.
[0058] As shown in Figure 5, when the mass ratio of Ni in the test material is constant, the hardness of the test material tends to increase as the mass ratio of Pd increases. Also, when the mass ratio of Pd in the test material is constant, the hardness of the test material tends to increase as the mass ratio of Ni in the test material increases. From the perspective of maintaining the hardness of the test material at 200 HV or higher when the mass ratio of Ni in the test material is 1 mass%, it can be said that the mass ratio of Pd in the test material needs to be 20 mass% or higher.
[0059] As shown in Table 2, in all of Examples 1 to 20, the thickness of the diffusion layer was 200 μm or less. In particular, in Examples 1 to 11, where the test material contained Ni instead of Pt, the thickness of the diffusion layer was 70 μm or less. In contrast, in Comparative Examples 1 to 3, the thickness of the diffusion layer was greater than 200 μm. From the comparison between Examples 1 to 20 and Comparative Examples 1 to 3, it can be said that when the test material contains at least one of Ni and Pt, the diffusion of components contained in the test material into the solder can be suppressed compared to when the test material is a PdCuAg alloy or a PdCu alloy.
[0060] Figure 6 is a graph showing the relationship between the mass ratio of Ni contained in the test material and the thickness of the diffusion layer between the test material and the solder, for Examples 2-4, where the mass ratio of Pd in the test material is 45% by mass; Examples 5-8, where the mass ratio of Pd in the test material is 35% by mass; and Examples 10-11, where the mass ratio of Pd in the test material is 25% by mass. Figure 7 is an enlarged view of a portion of the graph shown in Figure 6.
[0061] In Figures 6 and 7, the horizontal axis of the graphs represents the mass ratio (in mass%) of Ni contained in the test material. The vertical axis of the graphs represents the thickness (in μm) of the diffusion layer between the test material and the solder.
[0062] The circular plots in Figures 6 and 7 represent the plots for Examples 2-4, where the mass ratio of Pd in the test material is 45% by mass. The square plots in Figures 6 and 7 represent the plots for Examples 5-8, where the mass ratio of Pd in the test material is 35% by mass. The triangular plots in Figures 6 and 7 represent the plots for Examples 10-11, where the mass ratio of Pd in the test material is 25% by mass.
[0063] The curves associated with the circular plot where the mass ratio of Pd in the test material is 45% by mass, the curve associated with the square plot where the mass ratio of Pd in the test material is 35% by mass, and the curve associated with the triangular plot where the mass ratio of Pd in the test material is 25% by mass are curves that can be estimated from the trend of the plot where the mass ratio of Pd in the test material is 35% by mass.
[0064] As shown in Figures 6 and 7, when the mass ratio of Pd in the test material is constant, the thickness of the diffusion layer tends to increase as the mass ratio of Ni in the test material decreases. Also, when the mass ratio of Ni in the test material is constant, the thickness of the diffusion layer tends to increase as the mass ratio of Pd in the test material increases. From the perspective of keeping the thickness of the diffusion layer below 200 μm when the mass ratio of Pd in the test material is 25 mass%, it can be said that the mass ratio of Ni in the test material needs to be 0.1 mass% or more. From the perspective of keeping the thickness of the diffusion layer below 200 μm when the mass ratio of Pd in the test material is 35 mass%, it can be said that the mass ratio of Ni in the test material needs to be 0.5 mass% or more. From the perspective of keeping the thickness of the diffusion layer below 200 μm when the mass ratio of Pd in the test material is 45 mass%, it can be said that the mass ratio of Ni in the test material needs to be 3 mass% or more.
[0065] Figure 8 is a graph showing the relationship between the mass ratio of Pd contained in the test material and the thickness of the diffusion layer between the test material and the solder, for Examples 3, 6, and 10, and Comparative Example 3, in which the test material does not contain Pt but contains 10 mass% Ni.
[0066] In Figure 8, the horizontal axis of the graph shows the mass ratio (in mass%) of Pd contained in the test material. The vertical axis of the graph shows the thickness (in μm) of the diffusion layer between the test material and the solder.
[0067] The circular plots in Figure 8 represent the plots for Examples 3, 6, and 10, and Comparative Example 3, in which the test material does not contain Pt but contains 10% by mass of Ni. The curves attached to these circular plots are curves estimated from the trends of the plots.
[0068] As shown in Figure 8, when the test material does not contain Pt but contains Ni in a certain mass ratio, the thickness of the diffusion layer tends to increase as the mass ratio of Pd in the test material increases. From the perspective of keeping the thickness of the diffusion layer below 200 μm when the test material does not contain Pt but contains 10 mass% Ni, it can be said that the mass ratio of Pd in the test material needs to be 60 mass% or less.
[0069] Figure 9 is a triangular graph showing the relationship between the mass ratio of Pd, the mass ratio of Cu, and the mass ratio of at least one of Ni and Pt contained in the test material.
[0070] The edge of the triangular graph from the lower right vertex to the upper center vertex represents the mass ratio (unit: mass%) of Pd contained in the test material. The edge of the triangular graph from the upper center vertex to the lower left vertex represents the mass ratio (unit: mass%) of Cu contained in the test material. The edge of the triangular graph from the lower left vertex to the lower right vertex represents the mass ratio (unit: mass%) of at least one of Ni and Pt contained in the test material.
[0071] In the triangular graph of Figure 9, the hatched region indicates the range where the mass ratio of Pd is 15% to 60%, the mass ratio of Cu is 3% to 79.9%, and the mass ratio of at least one of Ni and Pt is 0.1% to 75%. The plots for Examples 1 to 20 are located within this hatched region. Based on the trends of the plots for Examples 1 to 20, it can be said that in any of the hatched regions, the diffusion of components contained in the test material into the solder can be suppressed compared to when the test material is a PdCuAg alloy or a PdCu alloy.
[0072] To evaluate the wear of the plunger tip when the plunger and solder are continuously energized over time, a first test pin containing the test material of Example 2, a second test pin containing the test material of Example 12, and a third test pin containing the test material of Comparative Example 1 were fabricated.
[0073] Figure 10 is a side view of the first, second, and third test pins. The shapes of the first, second, and third test pins will be explained using Figure 10.
[0074] Each test pin has a columnar portion 902 and a contact portion 904. The columnar portion 902 is cylindrical in shape. The contact portion 904 is provided at one end of the columnar portion 902. The contact portion 904 has a conical shape with a nearly pointed hemispherical tip with a radius of 0.05 mm.
[0075] As a continuous current test of the first, second, and third test pins, the tip of the contact area of each test pin was continuously in contact with a bar-shaped Sn-40Bi solder for 72 hours at a temperature of 120°C, and a current of 1A was passed through it. The tips of each test pin after the continuous current test were observed using a scanning electron microscope (SEM).
[0076] Figure 11 shows an SEM image of the tip of the contact area of the first test pin after a continuous energization test. Figure 12 shows an SEM image of the tip of the contact area of the second test pin after a continuous energization test. Figure 13 shows an SEM image of the tip of the contact area of the third test pin after a continuous energization test.
[0077] As shown in Figure 11, the first test pin showed almost no wear at the tip of the contact area compared to the second and third test pins.
[0078] As shown in Figure 12, the wear at the tip of the contact area was suppressed in the second test pin compared to the third test pin.
[0079] As shown in Figure 13, the third test pin showed more wear at the tip of the contact area compared to the first and second test pins.
[0080] Based on the results described above, it can be said that when the plunger contains at least one of Ni and Pt, wear on the tip of the plunger can be suppressed when the plunger and solder are continuously energized over time, compared to when the plunger contains a PdCuAg alloy.
[0081] To evaluate the wear of the plunger tip when the plunger and solder are repeatedly energized, a fourth test pin containing the test material of Example 2, a fifth test pin containing the test material of Example 12, and a sixth test pin containing the test material of Comparative Example 1 were prepared.
[0082] The shapes of the fourth, fifth, and sixth test pins were identical to those of the first, second, and third test pins, except for the shape of the contact portion. The tips of the contact portions of the fourth, fifth, and sixth test pins had four points arranged at equal intervals around the central axis of the test pin.
[0083] For the current endurance test of the 4th, 5th, and 6th test pins, a flying probe tester was used to apply a 2A current for 20ms to the tip of the test pin contact area with a bar-shaped Sn-40Bi solder at a temperature of 125°C, repeating this 10,000 times. The contact resistance of the test pin was measured in each of the 10,000 cycles.
[0084] Figure 14 shows an SEM image of the tip of the contact area of the fourth test pin after the current endurance test. Figure 15 shows an SEM image of the tip of the contact area of the fifth test pin after the current endurance test. Figure 16 shows an SEM image of the tip of the contact area of the sixth test pin after the current endurance test.
[0085] As shown in Figure 14, the fourth test pin showed almost no wear at the tip of the contact area compared to the fifth and sixth test pins.
[0086] The length of the tip of the contact area of the fourth test pin after the current-hold endurance test was 2.5 μm shorter than the length of the fourth test pin before the current-hold endurance test. The average contact resistance of the fourth test pin over 10,000 cycles of the current-hold endurance test was 36.6 mΩ.
[0087] As shown in Figure 15, the wear at the tip of the contact area was suppressed in the fifth test pin compared to the sixth test pin.
[0088] The length of the tip of the contact area of the fifth test pin after the current-hold endurance test was 12.4 μm shorter than the length of the fifth test pin before the current-hold endurance test. The average contact resistance of the fifth test pin over 10,000 current-hold endurance tests was 38.4 mΩ.
[0089] As shown in Figure 16, the sixth test pin showed more wear at the tip of the contact area compared to the fourth and fifth test pins.
[0090] The length of the tip of the contact area of the sixth test pin after the current-hold endurance test was 17.4 μm shorter than the length of the sixth test pin before the current-hold endurance test. The average contact resistance of the sixth test pin over 10,000 cycles of the current-hold endurance test was 34.6 mΩ.
[0091] Based on the results described above, it can be said that when the plunger contains at least one of Ni and Pt, wear of the plunger tip can be suppressed when the plunger and solder are repeatedly energized, compared to when the plunger contains a PdCuAg alloy. Furthermore, when the plunger and solder are repeatedly energized, the contact resistance when the plunger contains at least one of Ni and Pt can be made approximately the same as the contact resistance when the plunger contains a PdCuAg alloy.
[0092] The following embodiments are provided according to this specification. (Aspect 1) Embodiment 1 is, Pd in an amount of 15% to 60% by mass, Cu in an amount of 3% to 79.9% by mass, At least one of Ni and Pt in an amount of 0.1% to 75% by mass, This is a probe that includes [something]. According to Embodiment 1, compared to cases where the probe contains an alloy of Pd, Cu, and Ag but does not contain either Ni or Pt, or cases where the probe contains an alloy of Pd and Cu but does not contain either Ni or Pt, the diffusion of components contained in the probe into the solder at the interface between the probe and the solder can be suppressed. [Explanation of symbols]
[0093] 10 sockets 10A socket 20. Items to be inspected 22 balls 30 Inspection boards 32 pads 100 probes 100A probe 100B probe 110 First Plunger 110A First Plunger 110B First Plunger 112A Extension part 114A Tip Head 120 Second Plunger 120A Second Plunger 120B Second Plunger 122A Proximal end 124A Hole 126A Locking part 130 tubes 130B Tube 140 Spring 140A Spring 140B Spring 200 Insulating Support 902 Pillar section 904 Contact area
Claims
[Claim 1] 15% by mass or more and 60% by mass or less of Pd; Cu of 3% by mass or more and 79.9% by mass or less; At least one of Ni and Pt in an amount of 0.1 mass% or more and 75 mass% or less; Including, At least Ag-free probe.
